2017
DOI: 10.1101/150656
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inducible, tunable and multiplex human gene regulation using CRISPR-Cpf1-based transcription factors

Abstract: Targeted and inducible regulation of mammalian gene expression is a broadly important research capability that may also enable development of novel therapeutics for treating human diseases. Here we demonstrate that a catalytically inactive RNA-guided CRISPR-Cpf1 nuclease fused to transcriptional activation domains can up-regulate endogenous human gene expression. We engineered drug-inducible Cpf1-based activators and show how this system can be used to tune the regulation of endogenous gene transcription in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…We used a nuclease-dead dCas12a (D832A) from Lachnospiraceae bacterium fused with tripartite VPR for targeted gene activation (Tak et al, 2017). To minimize the size of the construct, we used a minimized VPR (miniVPR) (Vora et al, 2018), which showed comparable activation in a TRE3G-GFP HEK293T reporter cell line (Figures S1A and S1B; Tables S1, S2, S3, and S4).…”
Section: The Split Cas12a System Enables Construction Of and Gates In Mammalian Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a nuclease-dead dCas12a (D832A) from Lachnospiraceae bacterium fused with tripartite VPR for targeted gene activation (Tak et al, 2017). To minimize the size of the construct, we used a minimized VPR (miniVPR) (Vora et al, 2018), which showed comparable activation in a TRE3G-GFP HEK293T reporter cell line (Figures S1A and S1B; Tables S1, S2, S3, and S4).…”
Section: The Split Cas12a System Enables Construction Of and Gates In Mammalian Cellsmentioning
confidence: 99%
“…Standard molecular cloning techniques were used to assemble constructs in this paper. Nuclease-dead (D832A) dCas12a from Lachnospiraceae bacterium and its crRNA backbone were modified from plasmids obtained from Addgene (#104567 and # 78742) (Tak et al, 2017;Kleinstiver et al, 2016). The leucine zipper was amplified from plasmids obtained from Addgene (#15304 and #15305) (Luan et al, 2006).…”
Section: Plasmid Cloningmentioning
confidence: 99%
See 1 more Smart Citation